The Abecedarian Approach to Social Competence Cognitive and Linguistic Intervention for Disadvantaged Preschoolers - Ramey, Craig T.; North Carolina Univ., Chapel Hill. Frank Porter Graham Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
After discussing the differences in the physical, social, and attitudinal environments of advantaged and disadvantaged children, this paper describes the educational settings and intervention practices that were designed as part of the Carolina Abecedarian Project to assist young disadvantaged children in attaining educational competence. An overview of the project's organization, conceptual framework and daily action plan is provided. Specific activities designed to help prepare children in the program for the social and behavioral demands of the public schools are described. The role of parents in the program is also described. Special emphasis is placed on the development of communication skills in preschool children. Strategies developed by the program to promote a particular kind and amount of verbal interaction between teacher and day care pupil are listed. Objectives of this language intervention approach and methods employed for achieving these objectives are outlined. Two examples of results from this program show that the program is accomplishing its goal of preventing retarded intellectual development and improving linguistic performance. Social policy implications for preschool intervention programs are considered. (Author/EB)
ERIC Note: Table 4, page 45a, has been deleted due to marginal legibility in the original document ; Best copy available.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Development; Communication Skills; Day Care; Educational Improvement; Educationally Disadvantaged; Intellectual Development; Intervention; Language Experience Approach; Linguistic Competence; Preschool Children; Preschool Education; Program Descriptions; North Carolina (Chapel Hill); Reports, Descriptive